THE ROLE OF BRANDING AGRICULTURAL PRODUCTS IN BETTER MARKET VALORIZATION - Uzelac, Ozren; Dukić Mijatović, Marijana; Lukinović, Mario (Economics of Agriculture, 2022)
The purpose of this paper is to consider role of branding agricultural products in better market valorization. The benefit of branding is especially significant for rural and insufficiently developed environment. The problems of rural environments are multidimensional, but revitalization and improvement of development leads to strengthening competitiveness of these areas. The higher price of products enables the increase of income of agricultural workers, as well as diversification of the rural economy and creation of conditions of better socioeconomic aspects in rural environments. Creation of a more desirable image of an agricultural product most often has a strong reflection on the area of origin, as well as on reformation of the social attitude towards that environment. Branded products and services have a higher market value, due to which legal aspects enabling not only branding, but maintenance of a brand as well, are of special significance.